Hostility, Anger, Psycho-emotional Factors and Cardiovascular Disease - G. F. Andreeva; V. M. Gorbunov (Рациональная фармакотерапия в кардиологии)
The review presents the main aspects of the relationship between psychoemotional factors, hostility, anger and cardiovascular diseases. The first chapter describes the main historical stages in the study of this problem, starting from the Middle Ages and ending with fundamental research of the 19-20 centuries. In the second part, the authors demonstrated that hostility/anger are a risk factor for the CVD development and affect the prognosis and course of CVD (hypertension, ischemic heart disease, various cardiac arrhythmias, etc.). In the third chapter, there were studies that found that high rates of hostility/ anger reduced the effectiveness of cardiovascular therapy. In the fourth part, there are the main correlation mechanisms of negative emotions, hostility/anger and the cardiovascular system, carried out through the relationships with the activation of the hypothalamic-pituitary-adrenal, autonomic nervous system, platelet activation, with the changes in the risk factors characteristics etc. In the final chapter, the authors suggested prospects for further study of the problem, probably associated with the assessment of behavioral interventions, pharmacological or complex effects on the severity of hostility/anger to reduce CVD mortality in individuals with high rates of hostility / anger.